Economic Evaluation of Oral Alendronate Therapy for Osteoporosis in Chinese Postmenopausal Women: The Impact of Medication Compliance and Persistence - Ruxu You; Zijie Liu (Frontiers in Pharmacology, 2020)
Objective: Prevalence of osteoporosis in Chinese postmenopausal women has significantly increased over the past decade and oral bisphosphonates are the most potent antiresorptive drugs. The purpose of the present research was to evaluate the cost-effectiveness of oral alendronate for individuals with osteoporosis. We also assessed the impact of medication compliance and persistence on economic outcomes of alendronate and potential economic evaluations of persistence-enhancing interventions.Methods: We constructed an individual-level state-transition model to project health outcomes and costs of oral alendronate for Chinese postmenopausal osteoporotic women. The impact of medication compliance and persistence on economic evaluation was addressed in various scenario analyses. Model inputs were derived from clinical trials and published sources, where available. Deterministic and probabilistic sensitivity analyses were conducted to explore the impact of uncertainties and assumptions on the cost-effectiveness results.Results: Compared with no treatment, alendronate treatment was associated with an additional 0.052 QALYs (quality-adjusted life-years) at an additional cost of USD 738, which yielded an incremental cost-effectiveness ratio (ICER) of USD 14,192.308/QALY. The ICER for the different scenarios (full compliance, full persistence, and both full persistence and full compliance) was USD 4,933.333/QALY, USD 3,006.849/QALY, and USD 2,049.822/QALY, respectively. One-way sensitivity analysis showed the ICER was most sensitive to variations in time horizon and residual effect. Probabilistic sensitivity analysis demonstrated that, at a willingness to pay of USD 29,340/QALY, the probability that oral alendronate therapy will be cost-effective is approximately 80%.Conclusion: The findings support the view that oral alendronate is cost-effective for the treatment of osteoporotic fractures in Chinese postmenopausal women. Medication persistence is found to have a greater impact on cost-effectiveness than compliance and interventions to improve persistence to be an efficient use of resources.